Spoke Dimension on the Motion Performance of a Floating Wind Turbine with Tension-Leg Platform - H. F. Wang; Y. H. Fan (Shock and Vibration)
The tension-leg platform (TLP) supporting structure is a good choice for floating offshore wind turbines because TLP has superior motion dynamics. This study investigates the effects of TLP spoke dimensions on the motion of a floating offshore wind turbine system (FOWT). Spoke dimension and offshore floating TLP were subjected to irregular wave and wind excitation to evaluate the motion of the FOWT. This research has been divided into two parts: (1) Five models were designed based on different spoke dimensions, and aerohydroservo-elastic coupled analyses were conducted on the models using the finite element method. (2) Considering the coupled effects of the dynamic response of a top wind turbine, a supporting-tower structure, a mooring system, and two models on a reduced scale of 1 : 80 were constructed and experimentally tested under different conditions. Numerical and experimental results demonstrate that the spoke dimensions have a significant effect on the motion of FOWT and the experimental result that spoke dimension can reduce surge platform movement to improve turbine performance.